Case report: Methicillin-resistant Staphylococcus aureus with penicillin susceptible (PS-MRSA): first clinical report from a psychiatric hospital in China - Yan, Fei; Yang, Mi; Sun, Yuting; Tang, Qin; Yuan, Lu (Frontiers in Medicine, 2024)
This case report documents the first instance of Penicillin-Susceptible Methicillin-Resistant Staphylococcus aureus (PS-MRSA) in a Chinese psychiatric hospital. The strain was isolated from a patient with Alzheimer’s disease who had a lower respiratory tract infection. Clinical and laboratory analyses, including mass spectrometry, antibiotic susceptibility testing, and whole-genome sequencing, confirmed the PS-MRSA strain. In this case, we systematically introduce the clinical symptoms, laboratory findings, and treatment responses associated with this PS-MRSA strain. This discovery offers a new perspective on our understanding of resistance mechanisms and expands our considerations for existing antibiotic treatments. It may fill a gap in the classification of MRSA strains, enhance the spectrum of MRSA resistance, and complete the therapeutic strategies for MRSA.